Relationship between sense of coherence, social support, negative attitude and parental stress among parents of children with autism in Selangor, Malaysia - Zulkipli, Anis Elina (2019)
Increased cases of autism have been identified in Malaysia in the past few years and there is sufficient evidence that parenting a child with autism potentially affects parents in several ways, including increased parental stress. However, research that explores the challenges and issues faced by these parents in Malaysia are limited. Therefore, the main objective of this study was to determine the relationship between sense of coherence, social support, negative attitude and parental stress among parents of children with autism in Selangor, Malaysia.